Biokimia Darah Tikus (Rattus norvegicus) Betina Ovariektomi setelah Perlakuan Ekstrak Daun Kaliandra Merah (Calliandra calothyrsus Meissn.) - Setyawati, Iriani; Wiratmini, Ngurah Intan; Wijayanti, Ni Putu Ayu Dewi (SIMBIOSIS, 2019)
Red calliandra ( Calliandra calothyrsus Meissn.) leaf have the potential as phytoestrogens. In this study, adult female ovariectomized rats (as a model of menopause women) were given calliandra leaf extract containing estrogenic flavonoids. This study was an experimental design with a Completely Randomized Design (CRD). Forty-five ovariectomized female rats were divided into five groups i.e. untreated control (K), and the treatment group given 80% of C. calothyrsus ethanolic leaves extract doses 25 mg/ kg bw (P1), 50 mg/ kg bw (P2), 75 mg/ kg bw (P3) and 100 mg/ kg bw (P4). The test suspension was given once a day at 24-hour intervals by gavage as much as 0.5 ml/rat/day for two months. At the end of the treatments, blood was collected for blood biochemical tests including hemoglobin levels, hematocrit values, blood glucose and proteins levels. The results showed that C. calothyrsus leaf extract did not negatively affect the health status of the animals through blood biochemical parameters, i.e. hemoglobin levels, hematocrit values, and glucose and protein levels of ovariectomized female rats.